Diagnosis, biology and epidemiology of oligometastatic breast cancer. (October 2021) - Lacaze, Jean-Louis; Aziza, Richard; Chira, Ciprian; De Maio, Eleonora; Izar, Françoise; Jouve, Eva; Massabeau, Carole; Pradines, Anne; Selmes, Gabrielle; Ung, Mony; Zerdoud, Slimane; Dalenc, Florence
Abstract: Does oligometastatic breast cancer (OMBC) deserve a dedicated treatment? Although some authors recommend multidisciplinary management of OMBC with a curative intent, there is no evidence proving this strategy beneficial in the absence of a randomized trial. The existing literature sheds little light on OMBC. Incidence is unknown; data available are either obsolete or biased; there is no consensus on the definition of OMBC and metastatic sites, nor on necessary imaging techniques. However, certain proposals merit consideration. Knowledge of eventual specific OMBC biological characteristics is limited to circulating tumor cell (CTC) counts. Given the data available for other cancers, studies on microRNAs (miRNAs), circulating tumor DNA (ctDNA) and genomic alterations should be developed Finally, safe and effective therapies do exist, but results of randomized trials will not be available for many years. Prospective observational cohort studies need to be implemented. Highlights: The incidence of oligometastatic breast cancer is unknown. Only one publication provides information regarding the biology of these cancers. Oligometastatic breast cancer and metastatic site definitions should be harmonized. Prospective observational cohort studies are needed.